ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOIDA DARI DAUN TUMBUHAN MUNDU (Garcinia dulcis (Roxb) kurz) - Samosir, Sri Rezeki (JIFI (Jurnal Ilmiah Farmasi Imelda), 2022)
The isolation and identification of flavonoid compounds from the leaves of the mundu plant (Garcinia dulcis (Roxb) kurz) as well as antibacterial and antioxidant activity tests have been carried out. The isolation process of flavonoid compounds was initiated by maceration process using methanol solvent, then continued with partitioning using ethyl acetate and n-hexane and the isolation process was continued using column chromatography. Determination of the structure using UV-Vis, IR, NMR and LC-MS/MS equipment. The flavonoid compound obtained has a weight of 12.0 mg and an Rf (Reterdation Factor) of 0.37. The result of interpretation of spectroscopic data shows that the flavonoid compound of the biflavonoid group is morreloflavone with the structural formula C30H23O11 and a molecular weight of 559.